EVALUASI SISTEM PENGELOLAAN LIMBAH PADAT BAHAN BERBAHAYA DAN BERACUN (B3) DI RUMAH SAKIT X SURABAYA - Muhammad Farhan Khatami; Mohamad Mirwan; Septin Aulidia (Yayasan Nusantara Hasana Berdikari, 2023)
Hospital waste is divided into two groups in general, namely medical waste and non-medical waste. Hospital medical waste is categorized as Hazardous and Toxic Materials (B3) waste as mentioned in Appendix I PP No. 101 of 2014 that medical waste has infectious characteristics. B3 waste can pose a danger to the environment and also an impact on the health of the community and other living things when disposed of directly into the environment. Good hospital B3 waste management is expected to minimize the impact caused. The purpose of this study was to evaluate the hospital B3 waste management system at X Hospital Surabaya according to applicable regulations. The method used is a qualitative method where the data obtained comes from the results of interviews, observations, and document reviews. The results of the research on B3 waste management at RS X Surabaya have met the achievement of 95.5% based on the regulations stated in the Regulation of the Minister of Environment and Forestry No. P.56 of 2015 both from the aspect of TPS Building which is in accordance with the provisions, aspects of sorting, storage has been carried out according to its characteristics, officers' knowledge of the use of PPE, waste handling and further treatment has been carried out by the 3rd party , as well as the reuse of used infusion bottles and used jerry cans has also been carried out.